Development of an infusion method for encapsulating ascorbyl palmitate in V-type granular cold-water swelling starch. (1st June 2017) - Dries, D.M.; Gomand, S.V.; Pycarelle, S.C.; Smet, M.; Goderis, B.; Delcour, J.A.
Highlights: Ascorbyl palmitate was complexed with granular cold-water swelling starch. Such starch contains V-type amylose helices with hydrophobic internal cavities. Encapsulation was accomplished by an infusion method in ethanolic media. The impact of experimental conditions and degree of V-type crystallinity was studied. Encapsulation was possible at relatively low temperatures. Abstract: Certain lipophilic components can be inserted very efficiently as guest molecule in the existing single helical amylose cavities in VH -type crystalline granular cold-water swelling starch (GCWSS). In the present study, ascorbyl palmitate (AscP) was used as a model guest compound. The impacts of temperature (20 and 60 °C) and ethanol [48 and 68% (v/v)] and AscP [1.0, 2.5, 5.0, 10.0% (w/w)] concentrations on encapsulation performance were investigated. First, native maize and potato starches were converted into VH -type GCWSS by aqueous ethanol [48% (v/v)] treatment at 95 °C. Exposing GCWSS to AscP induced the formation of inclusion complexes when a particular solvent (and temperature) environment was met. In 48% (v/v) ethanol, raising the treatment temperature to 60 °C did not significantly impact on the encapsulation performance. Maximum degrees of AscP encapsulation were 2.9 and 1.5% (w/w) for maize and potato starch, respectively, as determined by proton nuclear magnetic resonance measurements. As maize GCWSS contained more 'parent' VH -type crystals, it was capable of entrapping more AscP than potato GCWSS.